Work-Related Musculoskeletal Disorders Among Radiology and Ultrasound Technologists During Ramadan in Madinah, Saudi Arabia: A Cross-Sectional Study - Abdulkareem Algahtani; Jory Alluhaibi; Monaya Altamimi; Nada Almutairi; Manar Alrehaili; Dalia Alsahli; Bashair Alhummayani; Mohammed Asiri; Abdulhadi Alkulib; Sultan Alshoabi; Awadia Gareeballah; Awatif M. Omer; et al. (Healthcare, 2026)
Background: Radiology and ultrasound technologists are exposed to sustained static postures, repetitive movements, equipment handling, and patient-positioning tasks that increase the risk of work-related musculoskeletal disorders (WRMSDs). During Ramadan, increased healthcare demand associated with Umrah may further increase occupational workload in Madinah. Objective: To estimate the 7-day prevalence of WRMSDs and identify occupational factors associated with pain intensity among radiology and ultrasound technologists working during Ramadan in Madinah. Methods: A cross-sectional online survey was conducted among 237 radiology and ultrasound technologists working in Madinah during Ramadan 1447/2026. Participants were recruited using online convenience and snowball sampling through professional networks and social-media platforms. The survey included the Nordic Musculoskeletal Questionnaire (NMQ), a 0–10 Numeric Pain Rating Scale (NPRS), and demographic and occupational variables. Bivariate analyses and multivariable linear regression with robust standard errors were used to examine factors associated with pain intensity. Results: Overall, 89.5% of participants reported WRMSDs during the preceding 7 days. The lower back (56.5%) and neck (40.5%) were the most affected regions. Mean pain intensity was 5.55 ± 2.28. Higher pain intensity was associated, after adjustment for the variables included in the model, with older age, working as an ultrasound technologist, managing 11–20 or more than 30 patients per shift, and frequent night-shifts, with the strongest association observed among participants working at least three-night-shifts per week (B = 3.27, 95% CI 2.43–4.10). BMI, sex, years of experience and shift duration were not independently associated with pain intensity after adjustment. Conclusions: WRMSDs were highly prevalent among radiology and ultrasound technologists working during Ramadan in Madinah. Night-shift frequency and very high patient workload showed the largest occupational associations with pain intensity. These findings identify workload distribution and night-shift scheduling as potential areas for occupational health evaluation during periods of increased healthcare demand. Because of the cross-sectional design, the findings should be interpreted as associations rather than causal effects.